Three new species of the genus Nothrholaspis (Acari: Macrochelidae) from the Kelkit Valley, Turkey - Özbek Hasan Hüseyi̇n; Bal Durmuş Ali̇ (Zootaxa, 2015)
Three new species of mites of the genus Nothrholaspis Berlese, 1918 are described from specimens collected in the Kelkit Valley, Turkey—Nothrholaspis turcicus sp. nov., N. anatolicus sp. nov. and N. dogani sp. nov. The genus Nothrholaspis is recorded fromTurkey for the first time. An identification key for the new species and a tabular key for the all known species of the genus are included.